2023
DOI: 10.1002/solr.202300225
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Organic Solar Cells with Binary Additives Finely Regulated Active Layer Morphology and Improved Photovoltaic Performance

Abstract: Solvent additive can be used to regulate active layer morphology and improve photovoltaic performance of organic solar cells (OSCs). Herein, the PM6:Y6:PC71BM ternary bulk heterojunction OSCs are prepared by introducing 1,8‐diiodooctane (DIO) and 1‐chloronaphthalene (CN) as binary additives. On the basis of optimizing the photovoltaic performance with CN additive, the addition of trace amounts of DIO additive further improves the molecular packing of active layer and induces Y6:PC71BM acceptor on the surface o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…With the expectation of compromising the effect of the two kinds of additives, binary additives have been investigated in the past few years. 124–129 For instance, He and Zhao et al reported the OSC based on FTAZ:IDCIC (Fig. 2) with the binary additive, 1-CN&DIO, afforded a decent PCE of 13.58%, much higher than the counterparts with no additive (9.64%), DIO (9.76%), and CN (11.81%), respectively.…”
Section: Binary Additivesmentioning
confidence: 99%
“…With the expectation of compromising the effect of the two kinds of additives, binary additives have been investigated in the past few years. 124–129 For instance, He and Zhao et al reported the OSC based on FTAZ:IDCIC (Fig. 2) with the binary additive, 1-CN&DIO, afforded a decent PCE of 13.58%, much higher than the counterparts with no additive (9.64%), DIO (9.76%), and CN (11.81%), respectively.…”
Section: Binary Additivesmentioning
confidence: 99%
“…TEM that has a very high resolution <1 nm is a powerful electron microscopy-based technique, which is capable of yielding phase images and providing detailed phase morphological analysis with the help of energy-dispersive X-ray spectroscopy or electron energy-loss spectroscopy (EELS). [30,31] However, traditional bright-field TEM often fails to yield a highly contrasted phase image because of similar mass/electron densities of polymer donors and NFAs. Several electron microscopy-coupled techniques have thus been developed to generate enhanced image contrast for phase identification based on the electronic structure of materials in blend films.…”
Section: Electron Microscopy-based Techniquesmentioning
confidence: 99%